The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s1415-43662006000300001
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionamento econômico de profundidades e espaçamentos de drenos para a produção de cana-de-açúcar

Abstract: Com o aumento do preço da terra e da demanda por álcool/açúcar tem-se buscado o aumento da produtividade da cultura da cana e o aproveitamento de novas áreas para a produção, as quais podem necessitar de drenagem. Com isso, tornam-se importantes estudos de dimensionamento de sistemas de drenagem agrícola e sua avaliação econômica. O trabalho teve como objetivo avaliar economicamente, com o auxílio do modelo SISDRENA, a melhor combinação entre profundidade e espaçamento de valas, implantados em três tipos de so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…For sugarcane grown in clay soil, Askar et al [45] suggested drain depths of 1.4 to 1.8 m and spaces between drains ranging from 25 to 40 m. In clay-loam soil the drain pipes should be installed at spaces of between 55 and 70 m, with a corresponding drain depth between of 1.4 and 1.8 m. On the other hand" various authors [65,70,72,73] have determined that the best spaces of drains that presented the highest relative yield of sugarcane for clay loam, clay, silt clay loam soils were 60 m, 40 m and 30 m, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For sugarcane grown in clay soil, Askar et al [45] suggested drain depths of 1.4 to 1.8 m and spaces between drains ranging from 25 to 40 m. In clay-loam soil the drain pipes should be installed at spaces of between 55 and 70 m, with a corresponding drain depth between of 1.4 and 1.8 m. On the other hand" various authors [65,70,72,73] have determined that the best spaces of drains that presented the highest relative yield of sugarcane for clay loam, clay, silt clay loam soils were 60 m, 40 m and 30 m, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…where Y (decimal) represents the yield loss, estimated using the production function proposed by [90], which is dependent on the evapotranspiration deficit. Finally, the total relative yield (YT, decimal) is determined according to the methodology provided by the authors of [91], considering together the effects of water excess and water deficit, calculated by multiplying YRW (decimal) and YRD (decimal) More information is given in [64][65][66]70,72].…”
Section: Environmental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, the SISDRENA model simulates the performance of one-dimensional drainage systems (Miranda et al, 1998). Other researchers have used this model for different scientific questions (Silva et al, 2005;Duarte et al, 2002;Mingoti et al, 2006). However, there is a lack of research on using this model to simulate future scenarios of climate change.…”
mentioning
confidence: 99%
“…Empirically adopting drainage systems is often responsible for sugarcane failure. Thus, for the use of artificial drainage, studies are required with values representative of the physical-water and geometric properties of the soil profile, as well as physiological (MINGOTI et al, 2006). Studies of this nature with ratoon crops are still non-existent; the few we have are with cane plant, such as those by (TAVARES et al, 2017a, b;TAVARES et al, 2018a, b).…”
mentioning
confidence: 99%